Effect of cochlea damage on the detection of difference tone in signal envelope - Kordus, M. (Archives of Acoustics, 2006)
Recent studies have demonstrated that the detection of complex temporal envelopes relies on the perception of a distortion component generated by cochlear and postcochlear (central) nonlinearity. In the present study, 4-kHz carrier was modulated by tones f1 and f2 to produce the difference tone f3=f2-f1 in the amplitude modulation domain. Detection thresholds for canceling tone f3 were obtained for subjects with normal-hearing and hearing-impaired subjects. In three experimental conditions, monaural and binaural presentation of tones was used to test possible central origin of the nonlinearity in modulation domain. Modulation depth at threshold was measured as a function of the phase of the canceling component f3 varied from 0o to 270o in 45o steps. Results showed that level of canceling tone f3 was phase dependent at all signal frequencies. Thresholds for normal-hearing and hearing-impaired subjects were lower for the in-phase condition than for the antiphase condition. Results demonstrated that cochlear damage had no large effect on the nonlinearity in the AM envelope indicating that the distortion component must be generated by a more central non linear effects.